(untitled) (Takwil: Journal of Quran and Hadith Studies, 2025)
This study aims to formulate the concept of Al-Qur’anic eco-theology by integrating moderate Eco-Fiqh to preserve the natural environment. The global environmental crisis demands a change in human awareness and concrete actions towards the environment. Islam offers a theological foundation through the concepts of mizan (balance) and human responsibility as khalifah, which form the basis of ecological ethics. However, the implementation of these values requires strengthening at the level of adaptive fiqh based on the principle of religious moderation (wasathiyah). This study uses a descriptive qualitative approach with a literature review. Data were collected by analyzing primary and secondary literature on ecotheology, Eco-Fiqh, and religious moderation. This study fills a gap in the literature that has not yet integrated Eco-Fiqh and the principle of moderation as a coherent approach to environmental preservation. The novelty of this research lies in the integrative formulation between Al-Qur’an ecotheology and moderate Eco-Fiqh, which is systematically formulated and directed towards practical implications. The results of this study are expected to enrich the moderation Eco-Fiqh knowledge base and provide practical contributions to strengthening the conservation movement based on inclusive and sustainable Islamic values.